2013
DOI: 10.4314/jafs.v10i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Cooperatives in Small Scale Amaranthus Production in Kwara State Nigeria

Abstract: The study assessed cooperative in small scale amaranthus vegetable production in Kwara State, Nigeria with reference to cooperator and non-cooperator amaranthus vegetable farmers. Specifically, the study looked at the costs and returns to amaranthus vegetable farming for both groups and the effect of cooperative membership on the amaranthus vegetable farmers' output. A three stage sampling procedure was employed to collect data from 140 (70 cooperator and 70 non cooperator) vegetable farmers using a well struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This is in line with studies by Agbonlahor et al [24] Agbo [25] which noted that most cooperative members in Nigeria indicated that their major reason for joining cooperatives was to access credit facilities and other farm-inputs thus affirming that access to funds remains the major economic benefit farmers expect from agro based cooperatives in Nigeria. Studies by Omotesho et al [3] Omoregbee and Okojie [26] also observed that over the years, there has been an increase in the formation of agro based cooperatives evident in the increasing number of registered agro based cooperatives in the various states in Nigeria. However they observed that most of these cooperatives were formed with the sole aim of obtaining funds with most of them disappearing on obtaining the expected funds.…”
Section: Review Of Agricultural Cooperatives In Nigeriamentioning
confidence: 94%
See 3 more Smart Citations
“…This is in line with studies by Agbonlahor et al [24] Agbo [25] which noted that most cooperative members in Nigeria indicated that their major reason for joining cooperatives was to access credit facilities and other farm-inputs thus affirming that access to funds remains the major economic benefit farmers expect from agro based cooperatives in Nigeria. Studies by Omotesho et al [3] Omoregbee and Okojie [26] also observed that over the years, there has been an increase in the formation of agro based cooperatives evident in the increasing number of registered agro based cooperatives in the various states in Nigeria. However they observed that most of these cooperatives were formed with the sole aim of obtaining funds with most of them disappearing on obtaining the expected funds.…”
Section: Review Of Agricultural Cooperatives In Nigeriamentioning
confidence: 94%
“…Studies by Mai-Lafia and Obaka [19] pointed out that agricultural marketing cooperatives are involved with the joint marketing of agricultural products through the provision of value adding activities such as processing, sorting, grading, packaging, etc., necessary to transform agricultural produce in the form required by consumers. Omotesho et al [3] explained that most of these marketing efforts such as processing, grading, packaging, storage, etc., cannot be efficiently carried out by these individual small scale farmers, hence the need for them to form cooperatives to jointly carry out these functions to enjoy economies of scale and profit maximisation. Works by Adefila , [20] Chambo [21] also noted that agricultural marketing cooperatives help motivate small scale farmers to make entry into markets which they would not have ventured into as individual farmers, providing them with assured market for their produce, better production decisions and better prices for their agricultural produce.…”
Section: Role Of Agricultural Marketing Co-operatives In Agricultural...mentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, Farmers' Cooperative Societies (FCSs) provide a veritable platform to improve the living conditions of farmers through increased agricultural production and productivity in sub-Saharan Africa (SSA). According to Omotesho (2008), cooperative societies are the most effective vehicles for efficiently mobilizing production resources for accelerated rural development. They allow for the harnessing and pooling of millions of smallholder farmers' resources to enable them to enjoy the advantages of economies of scale (Onugu & Abdulahi, 2012).…”
Section: Introductionmentioning
confidence: 99%